Benjamin Franklin : a collection of critical essays - Barbour, Brian M. (New Jersey : Prentice-Hall, 1979)
This outlook, presented in the Autobiography and in a handful of congruent essays.
Introduction -- Franklin's character -- The spirit of capitalism -- Franklin and the divided heritage and puritanism -- Franklin and emerson -- The printer as a man of letters -- Benjamin Franklin: The making of an american character -- Benjamin Franklin -- The autobiography of benjamin franklin -- Franklin and spiritual autobiography -- Franklin and the shaping of american ideology.
Includes bibliographical references.
Keywords: AMERICAN LITERATURE -- COLONIAL PERIOD